2005
DOI: 10.3348/kjr.2005.6.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Immediate Procedure-Related Complications of Failed Hemodialysis Access Recanalization

Abstract: Endovascular procedures are becoming the standard type of care for the management of hemodialysis vascular access dysfunction. As with any type of medical procedure, these techniques can result in procedure-related complications, although the expected number of complications is low. The clinical extent of these complications varies from case to case. Management of these cases depends on the clinical presentation. Major complications such as vein rupture, arterial embolism, remote site bleeding or hematoma, sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Reported procedure-related complications include puncture site problems such as local hematoma and subcutaneous pseudoaneurysm, venous rupture or dissection, arterial embolism, bleeding or hematoma at remote site, and symptomatic pulmonary embolism ( 20 , 26 ). Some of these problems were followed with observation and others required surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Reported procedure-related complications include puncture site problems such as local hematoma and subcutaneous pseudoaneurysm, venous rupture or dissection, arterial embolism, bleeding or hematoma at remote site, and symptomatic pulmonary embolism ( 20 , 26 ). Some of these problems were followed with observation and others required surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is an additional predicament that can potentially complicate balloon rupture. Balloon fragmentation with the subsequent risk of fragment retention or embolization has also been reported . However, in our cohort, we did not encounter this complication.…”
Section: Discussionmentioning
confidence: 55%
“…It was reported that 4% (4/107) of patients who underwent surgical thrombectomy suffered a post-operative infection and required a repeated procedure and antibiotic therapy (20). Endovascular interventions are associated with embolization (21-23), in particular arterial emboli, which occur in >6% of patients receiving percutaneous declotting (24,25). To avoid severe adverse effects, a methodical approach to patient selection is important and patients with contraindications for each procedure should be excluded (2,24).…”
Section: Discussionmentioning
confidence: 99%